2021
DOI: 10.1111/jog.14766
|View full text |Cite
|
Sign up to set email alerts
|

A survey of Japanese interns to prepare for mandatory clinical training in obstetrics and gynecology

Abstract: Aim Obstetrics and gynecology (Ob/Gyn) training became compulsory for Japanese physician interns from April 2020 to improve medical competence in treating women's diseases. This study aims to understand the Ob/Gyn training needs of postgraduate year 1–2 physicians (interns) and thereby improve training efficiency. Methods This study was administered to interns at Ob/Gyn training facilities from December 2019 to February 2020. An original questionnaire was used to evaluate their assessment of training needs. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Meanwhile, 93.6% of the tutors who responded to the post‐event questionnaire said that they felt this event would be a catalyst for future recruitment. Onodera et al 7 showed that the quality of instruction, the atmosphere, and interpersonal relationships in OB‐GYN departments are essential factors for effective OB‐GYN training. However, OB‐GYNs working at medical universities have multiple tasks, such as clinical practice and research, and have limited time to participate in recruiting activities.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, 93.6% of the tutors who responded to the post‐event questionnaire said that they felt this event would be a catalyst for future recruitment. Onodera et al 7 showed that the quality of instruction, the atmosphere, and interpersonal relationships in OB‐GYN departments are essential factors for effective OB‐GYN training. However, OB‐GYNs working at medical universities have multiple tasks, such as clinical practice and research, and have limited time to participate in recruiting activities.…”
Section: Discussionmentioning
confidence: 99%